Penerapan Importance Performance Analysis (IPA) untuk Meningkatkan Kualitas Pelayanan pada Restoran Solaria - Restu Purwaningtyas; Endang Silaningsih; Wahyuni Diandra Maharani; Andi Hardiansyah; Resti Amelia (MENAWAN : Jurnal Riset dan Publikasi Ilmu Ekonomi, 2025)
Community service initiatives often struggle to meet the needs of beneficiaries. This study explores the application of Importance Performance Analysis (IPA) to improve the effectiveness of community service programs, using Solaria Restaurant’s customer service efforts as a case study. The research investigates the gap between beneficiaries’ expectations and their perceptions of delivered services. Data is collected through surveys administered to a sample of Solaria Restaurant patrons who have benefitted from the restaurant’s community service programs. By analyzing the importance and performance ratings provided by participants, the study identifies areas for improvement within Solaria’s service delivery. This research demonstrates the value of IPA as a tool for enhancing community service programs. By aligning service delivery with beneficiary expectations, organizations can maximize the impact of their efforts and create more meaningful community engagement.